A Further Look Into The Integration of Strategic Business Sustainability and the Communication of Business Sustainability Beyond Reporting - Lew, Stephen Joo Wei (2015)
There has been continuous growth in the area of sustainability reporting globally, and in the ASEAN region, Malaysia has been found to have the distinction of being the country with the highest number of sustainability reports produced. This growth is in part due to firms attempting to address the ever evolving relationship between businesses and its stakeholders over the decade which has given rise to a variety of ethical, economic, social, and even environmental challenges (ACCA, 2010; Carroll and Bucholtz, 2014). However, despite the high level of adoption, some of the issues which firms face in the implementation of business sustainability is the numerous varied definitions and constructs regarding the concept of business sustainability, causing firms to have numerous interpretations of the concept. In addition, not many firms were found to have an integrated strategy which is aligned with organizational goals (Lopez et al., 2007; PwC, 2013). The group study portion has been conducted in attempting to address these problems, however, the study designed primarily to analyse and draw conclusions from publically available financial and non-financial information in the annual or sustainability reports of Malaysian firms. Therefore, as a further extension of the group study, this portion of the study would be a conceptual review on further examining the strategic formulation of business sustainability strategy, as well as the strategic communication of business sustainability initiatives of firms to their stakeholders beyond annual and sustainability reporting. In addition, since the increase of business sustainability adoption and reporting is due to regulatory and governmental intervention, this study would also explore on further initiatives which can be taken by regulators to promote business sustainability in the Malaysian context.